Targeted nanotherapeutics in the prophylaxis and treatment of thrombosis - Priya V.; Viswanadh M.K.; Mehata A.K.; Jain D.; Singh S.K.; Muthu M.S. (My University, 2025)
Currently available anti-thrombotic therapy for the prophylaxis and treatment of arterial and venous thrombosis includes intravenous administration of anti-thrombotic drugs which lead to severe bleeding risks such as cerebral hemorrhage and stroke. Targeting approaches that utilize nanosystems to reach the thrombus sites are emerging to increase the local effect of anti-thrombotic drugs, as well as to decrease these severe bleeding complications by diminishing the systemic availability of these drugs. This review emphasizes the emerging targeted nanomedicines (liposomes, micelles, polymeric nanoparticles, material bases nanoparticles and other biological vectors) for the prophylaxis and treatment of thrombotic events as well as multifunctional nanomedicines for theranostic applications. Nanomedicine offers a promising platform for a smart, safe, and effective approach for the management of thrombosis. © 2021 Future Medicine Ltd. © 2021 Future Medicine Ltd.. All rights reserved.